Climate change and seed system interventions impact on food security and incomes in East Africa - Otieno, Gloria Atieno; Ogola, Robert John O.; Recha, Tobias; Mohammed, Jemal Nurhisen; Fadda, Carlo (MDPI, 2022)
Climate change is challenging agricultural productivity, especially in Africa. Adoption of improved or diverse seed varieties is a promising strategy to achieve increased yields, support food security and reduce poverty under climate change in East Africa. However, rigorous impact evaluations linking the contributions of improved seeds to the welfare of households have been limited. This paper evaluates the impact of diversified seed systems on farm household production, sales, income, consumption and seed storage in Kenya and Uganda. It applies four-cell analysis to explore the intra-specific diversity of crops within farming systems, using primary data obtained from a random sampling of 207 treatment households and 87 control households. Propensity score matching was used to investigate the relationship between adoption of improved seeds and changes in production, sales, income, consumption, seed storage and food security. Econometric results indicate that treatment households using improved seeds saw a significant positive impact on income from bean seed sales, sorghum and millet consumption, bean livestock feed and maize and millet seed stored. We conclude that increasing seed diversity helps farmers cope with climate change and increases productivity, food availability, incomes and food security. Partnerships among seed improvement stakeholders need to be enhanced to ensure a continued supply of appropriate seeds to farmers.